2001
DOI: 10.1021/jf0013712
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Structurally Novel Antimutagenic Flavonoids from Spinach (Spinacia oleracea)

Abstract: Thirteen compounds, isolated from spinach (Spinacia oleracea), acted as antimutagens against the dietary carcinogen 2-amino-3-methylimidazo[4,5-f]quinoline in Salmonella typhimurium TA 98. The antimutagens were purified by preparative and micropreparative HPLC from a methanol/water (70:30, v/v) extract of dry spinach (commercial product) after removal of lipophilic compounds such as chlorophylls and carotenoids by solid-phase extraction (SPE). Pure active compounds were identified by instrumental analysis incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 28 publications
3
48
0
Order By: Relevance
“…It was demonstrated that UV spectra and first-order ESI mass spectra allowed a fast characterisation of flavonoids even if reference compounds were not at hand or available. Identification of phenolics separated after HPLC was also carried out using fast atom bombardment mass spectrometry [154,155] and electron impact mass spectrometry [154]. On the other hand, matrix-assisted laser desorption/ionisation mass spectrometry has been employed for qualitative and quantitative analysis of anthocyanins in foods [156].…”
Section: Hplc Detectionmentioning
confidence: 99%
“…It was demonstrated that UV spectra and first-order ESI mass spectra allowed a fast characterisation of flavonoids even if reference compounds were not at hand or available. Identification of phenolics separated after HPLC was also carried out using fast atom bombardment mass spectrometry [154,155] and electron impact mass spectrometry [154]. On the other hand, matrix-assisted laser desorption/ionisation mass spectrometry has been employed for qualitative and quantitative analysis of anthocyanins in foods [156].…”
Section: Hplc Detectionmentioning
confidence: 99%
“…Despite these inroads, mass spectrometric analysis has not yet reached the point where de novo identification of flavonoids is possible. Analysis of flavonoids in plant extracts [34 -40], foodstuffs [41][42][43][44][45][46], and human biological fluids [47][48][49] have been reported, but the identity of flavonoids in these complex matrices generally must be confirmed by comparison with commercial standards. Otherwise only tentative identifications can be made, particularly in terms of saccharide location and identity, unless supplementary analytical methods, such as UV, FTIR, or NMR spectroscopy, are employed.…”
mentioning
confidence: 99%
“…There are only a few papers describing the biological effects of flavonoids isolated from spinach, such as antioxidative and antimutagenic activities [5][6][7]. Very recently, Ishida et al [19] reported the inhibitory activity of aqueous spinach extract on the degranulation of RBL-2H3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous papers relating to spinach constituents, it contains a various compound such as nutrients, vitamins, minerals and polyphenolic compounds. To date, it has been reported that spinach has antioxidant effect, anti-mutagenic and anti-inflammatory effects [5][6][7][8][9][10][11]. The antioxidant effect of spinach is reported to be mainly due to the flavonoid compounds such as spinacetin glucoside, patuletin glucoside and dioxol flavonoid [5,7,10].…”
Section: Introductionmentioning
confidence: 99%